Board Characteristics Best Practices and Financial Performance. Evidence from the European Capital Market - Victor-Octavian Müller; Ionel-Alin Ienciu; Carmen Giorgiana Bonaci; Crina Ioana Filip (Amfiteatru Economic)
This study investigates board characteristics best practices in the particular context of European listed companies. The theoretical grounding of the paper is done by discussing board composition and board compensation related studies, mainly belonging to the corporate governance literature. The main objective of the paper is to contribute to the debate on whether certain board characteristics can be documented to represent best practices. In doing so, we investigate if such board characteristics significantly influence companies’ financial performance. We use econometric regression models in order to assess the impact of a series of corporate governance board related characteristics on the performance of companies (constituents of FTSE100) listed on the largest European capital market (London Stock Exchange), for the 2010-2011 period. An accounting measure of operating performance, namely the operating return on assets (ROA), is used. The profoundness of a potential impact of corporate board characteristics on companies’ performance is investigated by considering both contemporaneous and subsequent operating performance. Results document best practices through the existence of several significant associations between considered board characteristics and firm performance